The Influence of Product Innovation on Investment Interest Through Business Networks As an Intervening Variable in Startup Companies in Indonesia - Putra, Rizky; Lumbanraja, Prihatin; Absah, Yeni; Silalahi, Amlys (KnE Social Sciences, 2024)
In carrying out innovation, all human resources in startup companies need the same market orientation to unite the perception of startup company management to jointly understand customer desires and create original values in the new products produced. This research is the first to discuss the impact of innovation on investment interest in startup companies through business networks, especially startup companies in Indonesia. Therefore, this research is very suitable to be carried out as an effort to develop knowledge, especially regarding the impact of product innovation on investor interest in startup companies in Indonesia. Of course, this point is novel, so this research is worth doing. The population in this study was 2419 with a sample size of 300 respondents. The technique used is SEM PLS. The results of the study show that product innovation has a significant and influential effect on investment interest in startup companies in Indonesia. Product innovation has a significant impact on business networks in startup companies in Indonesia. Business networks have a significant influence on investment interest in startup companies in Indonesia. Product innovation has a significant influence on investment interest in startup companies in Indonesia through business networks as an intervening variable. Keywords: product innovation, investment interest, business network